Yield curve and its impact on predicting economic growth in Uzbekistan - Azimov Utkirbek Qilich ugli (Zien Journals, 2022)
One of the most important instruments of monetary policy of the state to regulate the country's economy is the open market operations of the Central Bank. Various mechanisms are used to assess the success of these operations. One of these mechanisms is the yield curve. The country influences its monetary policy through the sale and purchase of securities in domestic and foreign markets. The rate of return on bonds issued by the Central Bank is formed as a result of supply and demand for it. Through this change in the level of profitability, international investors will be able to conclude about the current and future state of the country. This article constructs the equation of the yield curve on government securities and thus analyzes the current state of the REPO operations market.
Keywords: yield curve; treasury bonds; economic growth; Repo operations